Strategi Peran Pemasaran dalam Meningkatkan Penjualan: Studi Kasus RM Bunda di Kota Medan - Yanri Girsang; Amelisa Sipayung; Putri Gabryela; Dionisius Sihombing; Fadli Agus Triansyah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to analyze the operational strategies, promotional practices, and implementation of business ethics at the small and medium enterprise (SME) Warung Makan (RM) Bunda in Medan City. The research employs a case study approach with a qualitative-descriptive method. Primary data were collected through semi-structured interviews with the owner, employees, and selected customers using purposive sampling, complemented by participatory observation and document analysis such as sales records, simple financial reports, and promotional materials. Data were analyzed through inductive and deductive coding processes to identify key themes, including understanding of business ethics, implementation of marketing strategies, the impact of these strategies on customer loyalty and brand image, as well as challenges faced in business management. The validity of findings was strengthened through data source triangulation and member checks with key informants. The results indicate that the marketing and promotional strategies implemented have positively influenced the improvement of the business image and customer loyalty, although the SME still faces limitations in resources and market competition challenges. These findings provide important implications for the development of sustainable business strategies for SMEs in the culinary sector.